PENELITIAN TERHADAP PENYELESAIAN PERSELISIHAN ANTARA KARYAWAN DENGAN PERUSAHAAN MELALUI PHI - Yoshua Setiawan; Yogo Pamungkas (Fakultas Hukum Universitas Trisakti, 2022)
In order to attract consumer interest, sometimes the marketing of a product provides Termination of employment frequently violates current standards, and the case filed also has formal flaws. The dispute case in the PHI Decision Number 169/Pdt.Sus-PHI/2017/PN Mdn relates to the layoff rules, which are not in accordance with the applicable regulations. The question of whether the resolution of labor disputes between PT Raya Padang Langkat (PT RAPALA) employees is in conflict with Law No. 2 of 2004 regarding PPHI and Regulation of the Minister of Manpower and Transmigration of the Republic of Indonesia Number 17 of 2014 and Is the resolution of layoff disputes between PT Raya Padang Langkat (PT RAPALA) against its employees through mediation based on Decision Number 169/Pdt.Sus-PHI/2017/PN Mdn. already following the laws and regulations in the field of manpower. To get answers to these problems, it is carried out using normative legal research methods, which are based on secondary data, analyzed qualitatively, and conclusions drawn using deductive methods. The conclusion of this decision study is that the judge's decision does not follow the applicable rules and competence of the PHI is that it is not authorized to handle layoff cases because of procedures or steps that were violated before being submitted by the Plaintiff.